Optimalisasi Budaya Literasi Melalui Perpustakaan Sekolah Di Masa Pandemi - Astuty, Widy (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This research is the extent to which efforts to optimize literacy culture through school libraries during the Covid-19 pandemic carried out by SD N 1 Pageraji Korwilcam Dindik Cilongok, Banyumas district. Data collection methods used in this study include: interviews, observation, and documentation. The data analysis technique is reduction, data presentation, and drawing conclusions. Programs in an effort to cultivate a literacy culture are compiled periodically, the daily program that has been implemented is by holding non-lesson book reading activities before learning begins, by sharing literacy corners throughout the school environment. The weekly program includes posting pictures / stories of activities on social media and making scheduled visits to the school library. Monthly program by making observation forms to assess students' progress in literacy. Semester program implemented by giving awards to teachers and students. These programs are implemented with a pattern of cooperation from all elements, namely the principal, teachers, education personnel, which will make the school library utilization program implemented properly.